The importance of developmental assets in HIV prevention behaviors among young black men who have sex with men (MSM) - Boyd, Donte T.; Harris, Orlando O.; Abu-Ba’are, Gamji Rabiu; Nelson, LaRon; Wilton, Leo (Scientific reports, 2024)
Developmental assets are critical to the health and wellbeing of youth. The current study examines the influence of developmental assets on PrEP use and HIV testing among YBMSM ages 18–24. Using a cross-sectional survey of YBMSM (N = 225), this study explored the role of external (e.g., family support, other adult support) and internal (e.g., personal responsibility) assets in explaining HIV prevention behaviors. Participants were recruited from Mechanical Turk (M-Turk) internet-based platform, social media sites, and community-based organizations. A path analysis was conducted to investigate the direct/indirect effects of internal and external assets on PrEP use and HIV testing. Family support (β = 0.40, p < 0.001) and other adult support (β = 0.22, p = 0 . 004) were both associated with personal responsibility. Personal Responsibility (β = 0.15, p = 0.03) and positive identity (β = 0.28, p < 0.001) were both associated with an increase HIV testing. Personal responsibility was positively associated with increased PrEP use (β = 0.30, p < 0.001). Our study results indicated that external assets play a role in helping to build internal assets that support increased HIV testing and PrEP use among YBMSM. Our findings suggest the need for strength-based interventions that help YBMSM build assets and increase HIV prevention behaviors.